2023
DOI: 10.1029/2023ja031448
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Thermospheric Traveling Atmospheric Disturbance During a Geomagnetic Storm

Abstract: Traveling atmospheric disturbance (TAD) plays an important role in the energy and momentum transfer from the lower atmosphere to the upper atmosphere, and from high‐ to low‐latitudes. It is common to observe TADs propagating toward low latitudes because of enhanced Joule heating and/or the Lorentz force at the high‐latitude ionosphere during storm time. However, energy or momentum variation associated with their equatorward propagation remains unclear. Two geomagnetic storms occurred on 7–8 September 2017 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
0
0
1
Order By: Relevance
“…The traveling ionospheric disturbances induced by magnetic storms could propagate some latitudinal structures toward the equator (Richmond, 1978). However, our results showed that the mid‐latitude peak on 24 April is an independent latitude feature, different from the oscillation feature generated by TID observed during this storm (Li et al., 2023). Moreover, SED usually refers to narrow enhanced TEC bands extending from the high‐density area at the mid‐latitudes in the local afternoon and dusk sectors to the higher latitudes in the noon sector (e.g., Aa et al., 2023; Coster et al., 2007; Foster, 1993).…”
Section: Discussioncontrasting
confidence: 99%
“…The traveling ionospheric disturbances induced by magnetic storms could propagate some latitudinal structures toward the equator (Richmond, 1978). However, our results showed that the mid‐latitude peak on 24 April is an independent latitude feature, different from the oscillation feature generated by TID observed during this storm (Li et al., 2023). Moreover, SED usually refers to narrow enhanced TEC bands extending from the high‐density area at the mid‐latitudes in the local afternoon and dusk sectors to the higher latitudes in the noon sector (e.g., Aa et al., 2023; Coster et al., 2007; Foster, 1993).…”
Section: Discussioncontrasting
confidence: 99%